PENGHINDARAN PAJAK PADA BANK UMUM : DIPENGARUHI OLEH KARAKTER EKSEKUTIF, KUALITAS AUDIT, KOMITE AUDIT, KOMPENSASI RUGI FISKAL, DAN RETURN ON ASSETS - Putri, Vidiyanna Rizal (Jurnal Manajemen Dayasaing, 2020)
The purpose of this research is to determine the effect of the executive character, the quality of audit, audit committee, fiscal lost compensation, and return on assets towards tac avoidance. The researcher used executive character, quality of audit, audit committee, fiscal lost compensation, and return on assets as the independent variables that are estimated affect the dependent variable (tax avoidance) that is represented through Cash Effective Tax Rate (CETR).             This research was conducted at banking company that has already registered in BEI during 2015-2019. This research using a secondary data and used purposive sampling method so that researcher got 21 banks as the sample and 98 observation after the outlier.             The result of this research shows that executive character gave a significant negative impact to tax avoidance. Meanwhile, the fiscal lost compensation gave a significant positive towards tax avoidance. Furthermore, the audit quality, audit committee, and return on assets do not affect to the tax avoidance.